2011
DOI: 10.1016/j.clim.2011.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of interferon-gamma-producing multifunctional CD4+ T-cells and dysfunctional CD8+ T-cells by glypican-3 peptide library in hepatocellular carcinoma patients

Abstract: Glypican-3 is a promising target for immunotherapy for hepatocellular carcinoma, but limited data exist regarding its immunogenicity in patients with diverse HLA types, immunogenicity for CD4+ T-cells, and the impact of inhibitory co-stimulation on glypican-3-specific T-cells. Using a 15mer overlapping peptide library for glypican-3, PBMC from patients with HCC were assessed ex vivo and after short-term in vitro expansion for tumor antigen-specific T-cell responses with and without blockade of PD-1/PD-L1 and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 52 publications
(74 reference statements)
2
17
0
Order By: Relevance
“…However, there are some data that suggest that DC function in hepatocellular carcinoma may be impaired [16]. In previous work, our laboratory showed that tumor antigen-specific CD8+ T-cells generated using 15mer peptide stimulation in cirrhotic patients with HCC were dysfunctional [17]. Similar findings have subsequently been reproduced by other groups [18].…”
Section: Introductionsupporting
confidence: 60%
See 2 more Smart Citations
“…However, there are some data that suggest that DC function in hepatocellular carcinoma may be impaired [16]. In previous work, our laboratory showed that tumor antigen-specific CD8+ T-cells generated using 15mer peptide stimulation in cirrhotic patients with HCC were dysfunctional [17]. Similar findings have subsequently been reproduced by other groups [18].…”
Section: Introductionsupporting
confidence: 60%
“…Antigen-specific T-cell IFNγ responses were examined after in vitro expansion in cytokine Elispot assay as previously described [17]. 5 × 10 4 antigen-expanded T-cells/well were restimulated with each peptide pool (1 μg/ml) in triplicates with positive (PHA) and negative (media) controls × 24 h in IFNγ Elispot plates.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In progressive HCC, the induction of CTL may be suppressed by regulatory T cells or immunosuppressive cytokines (33). It has been reported that GPC3-specific CTLs become exhausted in HCC, and that this exhausted state cannot be reversed by blocking the CTLA-4 and PD-1 inhibitory costimulation pathways (34). Further studies will be necessary to increase the clinical efficacy of immunotherapy for advanced HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Glypican-3 (GPC3), a cell surface heparin sulfate proteoglycan, is expressed by 84% of HCC and has been shown to be immunogenic in murine models and human cell culture 46 . Because the frequency of GPC3-specific T cells is low in the peripheral blood of HCC patients, optimized costimulatory conditions may be required for ex vivo expansion of these cells 47 . NY-ESO-1 is an additional cancer/testes antigen expressed in HCC.…”
Section: Immunotherapy Of Hccmentioning
confidence: 99%